Rhythm and ROS: Hepatic Chronotherapeutic Features of Grape Seed Proanthocyanidin Extract Treatment in Cafeteria Diet-Fed Rats - Antonio J. Cortés-Espinar; Néstor Ibarz-Blanch; Jorge R. Soliz-Rueda; Béatrice Bonafos; Christine Feillet-Coudray; François Casas; Francisca Isabel Bravo; Enrique Calvo; Javier Ávila-Román; Miquel Mulero (MDPI AG, 2023)
Polyphenols play a key role in the modulation of circadian rhythms, while the cafeteria diet (CAF) is able to perturb the hepatic biological rhythm and induce important ROS production. Consequently, we aimed to elucidate whether grape seed proanthocyanidin extract (GSPE) administration recovers the CAF-induced hepatic antioxidant (AOX) misalignment and characterize the chronotherapeutic properties of GSPE. For this purpose, Fischer 344 rats were fed a standard diet (STD) or a CAF and concomitantly treated with GSPE at two time-points (ZT0 vs. ZT12). Animals were euthanized every 6 h and the diurnal rhythms of hepatic ROS-related biomarkers, hepatic metabolites, and AOX gene expression were examined. Interestingly, GSPE treatment was able to recover the diurnal rhythm lost due to the CAF. Moreover, GSPE treatment also increased the acrophase of Sod1, as well as bringing the peak closer to that of the STD group. GSPE also corrected some hepatic metabolites altered by the CAF. Importantly, the differences observed at ZT0 vs. ZT12 due to the time of GSPE administration highlight a chronotherapeutic profile on the proanthocyanin effect. Finally, GSPE could also reduce diet-induced hepatic oxidative stress not only by its ROS-scavenging properties but also by retraining the circadian rhythm of AOX enzymes.